Identification of Two Novel Variants of the DMD Gene in Chinese Families with Duchenne Muscular Dystrophy - Wu J; Ren L; Huang X; Hu L; Zhang L; Xie D; Li Z; Han N; Huang S (Dove Medical Press, 2023)
Jiangfen Wu,1 Lingyan Ren,2 Xinyi Huang,3 Li Hu,2 Liangliang Zhang,2 Dan Xie,1 Zhimin Li,4 Naijian Han,4 Shengwen Huang1,2,5 1GuiZhou University Medical College, Guiyang, Guizhou, People's Republic of China; 2Prenatal Diagnosis Center, Guizhou Provincial People's Hospital, Guiyang, People's Republic of China; 3School of Medical and Life Sciences, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 4Annoroad Gene Technology (Beijing) Co., Ltd, Beijing, People's Republic of China; 5NHC Key Laboratory of Pulmonary Immunological Diseases, Guizhou Provincial, People's Hospital, Guiyang, People's Republic of ChinaCorrespondence: Shengwen Huang, Guizhou Provincial People's Hospital, Nanming District, Guiyang, People's Republic of China, Tel +8615185134701, Fax +86-851-85937194, Email hsw713@sina.comBackground: Duchenne muscular dystrophy (DMD), an X-linked recessive neuromuscular disorder, is caused by pathogenic variants in the DMD gene encoding a large structural protein in muscle cells.Methods: Two probands, a 6-year old boy and a 1-month old infant, respectively, were clinically diagnosed with DMD based on elevated levels of creatine kinase and creatine kinase isoenzyme. CNVplex and whole exome sequencing (WES) were performed for causal variants, and Sanger sequencing was used for verification.Results: CNVplex found no large deletions or duplications in the DMD gene in both patients, but WES discovered a single-nucleotide deletion in exon 48 (NM_004006.2:c.6963del, p.Asp2322ThrfsTer16) in the proband of pedigree 1, and a nonsense mutation in exon 27 (NM_004006.2:c.3637A>T, p.K1213Ter) in the proband of pedigree 2.Conclusion: The results of our study expand the mutation spectrum of DMD and enrich our understanding of the clinical characteristics of DMD. Genetic counseling was provided for the two families involved in this study.Keywords: DMD gene, exon 48, exon 27, whole exome sequencing, Duchenne muscular dystrophy